2019
DOI: 10.2147/cmar.s197747
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association between single nucleotide polymorphisms of <em>NOTCH</em> signaling pathway-related genes and the prognosis of NSCLC</p>

Abstract: Objective In this study, we analyzed the association between genetic variants of genes in the NOTCH signaling pathway and the prognosis of non-small-cell lung cancer (NSCLC) in the Chinese population. We also explored the interaction between genetic and epidemiological factors for the test group. Methods We performed genotyping of 987 NSCLC patients. Then, we used Cox proportional hazard models to analyze the associations between single-nucleotide polymorphisms (SNPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The Notch signaling pathway has an important regulatory role in a variety of tumor stem cells. Mutations in DNMT3a and NOTCH4 have been reported to be associated with better prognosis in patients with LUAD and NSCLC, respectively 73 , 74 . Similarly, the EGFR-TKI sensitivity of patients with these indicates a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Notch signaling pathway has an important regulatory role in a variety of tumor stem cells. Mutations in DNMT3a and NOTCH4 have been reported to be associated with better prognosis in patients with LUAD and NSCLC, respectively 73 , 74 . Similarly, the EGFR-TKI sensitivity of patients with these indicates a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype mutations in some key genes, including single nucleotide polymorphisms (SNPs), may cause disorder or over-activation of some specific signaling pathway, leading to tumor development and affect patients' prognosis (Xu et al, 2019). We have found that RAC1 polymorphisms are associated with platinum-based chemotherapy toxicity in lung cancer patients in our previous study (Zou et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…International Publisher [14][15][16][17][18][19][20]. It is important to discern some new biomarkers that can be used to predict the prognosis of platinum-based chemotherapy.…”
Section: Ivyspringmentioning
confidence: 99%